ULTRASOUND IMAGING OF POSTPARTUM UTERINE INVOLUTION AND OVARIUM DYNAMIC IN ONGOLE CROSSBREED COWS - Sukareksi, Hazar; Amrozi, Amrozi; Tumbelaka, Ligaya ITA (Universitas Syiah Kuala, 2019)
This study aimed to determine ultrasound of uterine involution and postpartum ovarian dynamics on Ongole Crossbreed Heifer (PO) associated with postpartum estrus signs. This study used 6 PO cows which were divided into primiparous group and pluripara group. The observation of uterine involution and ovarian dynamics was started from the first day postpartum using ultrasonography (USG) with a linear probe rectally, while the reproductive organs images were recorded every 2 days. The results showed that the time needed for all reproductive organs of 3 primiparous groups to complete the uterine involution after parturition was 37.331.15 days when the diameter of the vagina, cervix uterine, corpus uterine, left cornua, and right cornua uterine were 3.140.00 cm, 2.860.00 cm, 3.200.06 cm, 4.660.01 cm, and 4.660.01 cm, respectively. The time needed for all reproductive organs of 3 pluripara groups to complete uterine involution postpartum was 38.671.15 days with the diameter of the vagina, cervix uterine, corpus uterine, left cornua, and right cornua uterine 3.180.00 cm, 2.700.02 cm, 3.080.02 cm, 4.420.01 cm, and 4.420.01 cm, respectively. The average times of the first and second ovulation of primiparous cattle were 27.671.15 and 47.671.15 days postpartum, whereas in pluripara group was 28.331.15 and 48.331.15 days postpartum. At first ovulation all cows were not accompanied by signs of estrus, while at the second ovulation 2 primiparous cows and 1 pluripara cow showed less obvious signs of estrus, 1 primiparous cow and 1 pluripara cow showed signs of medium estrus, and 1 pluripara cow showed clear estrus signs.